Knowledge, attitude and training toward fire emergency safety preparedness among a Public School staff in Kedah - Ravanan, Jayaguru (2023)
Fire emergency safety preparedness measures in educational institutions are very important to reduce losses and damage due to fire. Since fire can happen at any time, itis important for all parties concerned to maintain a constant state of vigilance in theschool. Therefore, the main objective of this research paper is to examine therelationship between the knowledge, attitudes, and training possessed by staff working in public schools in the state of Kedah towards Fire Emergency Safety Preparedness. Researchers use quantitative methods through surveys to collect data. The study sampleconsisted of all staff at SMK XYZ, both academic staff and support staff. The total staff of SMK XYZ is 140 people. The estimated sample size for this study was based on Krejcie and Morgan's (1970) minimum sample size of 103 respondents, and the total usable questionnaire for this study was 124. Data analysis was performed using the Statistical Package for Social Science (SPSS) version 27. The researcher used descriptive analysis. and inference. The results of the demographic analysis show that there is a large male population, comprising 63.7 percent of respondents, 80.6 percent of whom are classified as regular academic teachers, and the majority of respondents are within 9–10 hours of the school premises. Based on inference analysis, it can be concluded that there is no statistically significant relationship between knowledge and fire emergency safety preparedness (β = -0.078, t = -0.867, p < 0.388), as well as no significant correlation between fire emergency safety attitude and preparedness (β = 0.121, t = 1.076, p < 0.284). However, a significant positive relationship exists between training and fire emergency safety preparedness (β = 0.351, t = 3.143, p < 0.002). Because training and fire emergency safety preparedness have a meaningful relationship, the school and related parties need to conduct training related to fire emergency safety preparedness because, for respondents, training is the most important thing in fire emergency safety preparedness. In addition, improvements also need to be made for knowledge and attitude so that respondents are also aware that a person's knowledge and attitude are important for fire emergency safety preparedness.